Debates Debates: Does Fixing Broken Windows Reduce Crime?
Recording of a debate on criminality and community policing in the U.S. Participants include: Ed Koch, Joseph McNamara, George Kelling, Nancy Mahon, Mort Feldman, Richard Curtis.